THE IMPORTANCE OF PLAY AND TOYS IN THE COMPREHENSIVE DEVELOPMENT OF PRESCHOOL CHILDREN (Scientific journal of the Fergana State University, 2024)
This article reveals the importance of play and the toys they love to play with in the development of preschool children. The game is not just to pass the time for children, it is a type of activity that is of inestimable importance in their development. However, games are not only educational for children, but also help to release their aggressiveness, aggression and energy.